Bloodstains on woven fabric: Simulations and experiments for quantifying the uncertainty on the impact and directional angles. (September 2017) - Agrawal, Prashant; Barnet, Laurel; Attinger, Daniel
Highlights: The impact of blood drops on a woven fabric was investigated. The distortion in impact and directional angle due to wicking in fabric is measured. The experimental and numerical methods can be used with any fabric. A numerical model was used to predict the growth of a bloodstain after drop impact. Numerical model shows good agreement with experiments on the final stain shape. Abstract: Bloodstain pattern analysis considers stains on various porous and non-porous surfaces, for the purpose of crime scene reconstruction. On non-porous surfaces, several studies relate the impact conditions of drops to the inspection of stain shapes. Stains on porous surfaces like fabrics have been relatively less explored. The phenomenon of imbibition of blood into the fabric after impact adds further complexity in retrieving information on the impacting conditions. The present work studies experimentally and numerically the formation of drip stains on a woven fabric. The proposed methodology first relies on Darcy's law to measure the imbibition characteristics of the fabric through a set of simple imbibition experiments. Next, the fabric properties are fed into a numerical model to predict the growth of the bloodstain after impact of a droplet. Experiments at different drop release heights and impact angles are compared with the numerical simulations. The uncertainties induced by the fabric on the determination of the impact and directional angles are explained and quantified.